Dar al-Hikmah Library, IIUM, hosted a memorial exhibition commemorating Allahyarham Emeritus Professor Tan Sri Ahmad Ibrahim - Tuan Ameri, Tuan Safa'at (Persatuan Pustakawan Malaysia, 2023)
In a solemn and meaningful event, the 19th Emeritus Professor Ahmad Ibrahim Memorial Lecture was conducted at the Senate Hall of the International Islamic University Malaysia on 24 July 2023. This annual lecture series serves as a commemoration of the esteemed contributions of Allahyarham Emeritus Professor Tan Sri Ahmad Ibrahim and revolves around the theme “Achieving Justice Through the Implementation of Shariah: Challenges and A Way Forward.”